Replication of Staphylococcal Resistance Plasmids - Kwong, Stephen M.; Ramsay, Joshua P.; Jensen, Slade O.; Firth, Neville (Frontiers in Microbiology, 2017)
The currently widespread and increasing prevalence of resistant bacterial pathogens is a significant medical problem. In clinical strains of staphylococci, the genetic determinants that confer resistance to antimicrobial agents are often located on mobile elements, such as plasmids. Many of these resistance plasmids are capable of horizontal transmission to other bacteria in their surroundings, allowing extraordinarily rapid adaptation of bacterial populations. Once the resistance plasmids have been spread they are often perpetually maintained in the new host, even in the absence of selective pressure. Plasmid persistence is accomplished by plasmid-encoded genetic systems that ensure efficient replication and segregational stability during cell division. Staphylococcal plasmids utilise proteins of evolutionarily diverse families to initiate replication from the plasmid origin of replication. Several distinctive plasmid copy number control mechanisms have been studied in detail and these appear conserved within plasmid classes. The initiators utilise various strategies and serve a multi-functional role in, i) recognition and processing of the cognate replication origin to an initiation active form, and ii) recruitment of host-encoded replication proteins that facilitate replisome assembly. Understanding the detailed molecular mechanisms that underpin plasmid replication may lead to novel approaches that could be used to reverse or slow the development of resistance.